1994
DOI: 10.1128/jcm.32.1.46-50.1994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new immunodiagnostic assay for Helicobacter pylori antibody detection: correlation with histopathological and microbiological results

Abstract: Infection with Helicobacter pylori has been associated with the pathogenesis of chronic active gastritis and gastric and duodenal ulcer disease. Detection of immunoglobulin G antibodies to H. pylori offers a simple alternative to direct detection of the organism in biopsied tissue by culture or histopathological methods. A rapid flow-through membrane-based enzyme immunoassay for the detection of human immunoglobulin G antibodies to H. pylori has been developed and evaluated. Clinical evaluations were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…ELISA for anti-H. hepaticus IgG1 and IgG2a in serum and IgA in bile and feces. An outer membrane antigen preparation of H. hepaticus was obtained by methods previously described for preparing H. pylori antigen (23). Briefly, H. hepaticus was cultured in Trypticase soy broth containing 5% fetal bovine serum for 48 h under microaerobic conditions as detailed above.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA for anti-H. hepaticus IgG1 and IgG2a in serum and IgA in bile and feces. An outer membrane antigen preparation of H. hepaticus was obtained by methods previously described for preparing H. pylori antigen (23). Briefly, H. hepaticus was cultured in Trypticase soy broth containing 5% fetal bovine serum for 48 h under microaerobic conditions as detailed above.…”
Section: Methodsmentioning
confidence: 99%
“…Serology is now widely used as a global method of diagnosis, and a variety of commercially available kits (27) or homemade methods (14) have been described. Most of these methods provide satisfactory results (1,15,20,27,37,43); however, significant improvements must be made before they can be considered as reference methods. Improvement of the antigenic preparations is the best way to improve the performances of the serological methods, but to date, there is no consensus as to the most appropriate composition of the preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Because it depends on both the characteristics of the strain and the host response, the serum antibody response to H. pylori could provide clues in predicting the severity of H. pyloriassociated diseases. Several studies have demonstrated a strong correlation between the levels of total anti-H. pylori immunoglobulin G (IgG) and the colonization of the gastric mucosa by the bacteria (1,27,37). However, the anti-H. pylori antibody patterns have been reported to show a high degree of polymorphism (2,16,30,33).…”
mentioning
confidence: 99%
“…Outer‐membrane antigen preparations of H. pylori and the novel Helicobacter sp. were obtained by methods previously described [39]. Briefly, a bacterial pellet from a 48‐hour broth culture (trypticase soy broth containing 5% fetal bovine serum) was washed in PBS three times and was examined for bacterial contaminants using Gram's stain and phase microscopy.…”
Section: Methodsmentioning
confidence: 99%